ANALYSIS OF HIV AND SYPHILIS TRANSMISSION PREVENTION PROGRAMS FOR ADOLESCENTS - Yusuf Hanafi Lubis; Susilawati Susilawati (Universitas Airlangga, 2023)
Background: Adolescents tend to want to try things they have never experienced, and the main contributing factor is curiosity and imitating what adults do, including sexuality. Aims: This study aimed to analyze the transmission prevention program of HIV and Syphilis for adolescents in North Sumatra. Methods: This study used an analytic survey approach with a cross-sectional design by taking 729 people as a sample, selected using quota sampling, from the total adolescent population (19.4% of the population of North Sumatra). Questionnaires produced using an online platform and adapted from The Prospero Network. The results were then transferred into a statistics-based application for descriptive data analysis, bivariate, and multi-level tests. Results: The study showed that >50% of the respondents took a quick, free laboratory test for HIV and syphilis and a reactive confirmation test through a health facility in both cases. Moreover, the results of multi-level statistical tests show models 1 and 2, namely the availability of syphilis screening referrals, have a 1-17 times higher risk of implementing HIV and syphilis programs in adolescents. Conclusion: Everything is interrelated with the implementation of HIV and Syphilis transmission prevention programs in adolescents. However, there is still a significant chance that it will not work. Therefore, the government and the community must work together to implement this program properly and consistently. Keywords: Adolescents, Health Program, HIV, Syphilis